'Indexing in Service of the Reader': Association of Southern African Indexers and Bibliographers (ASAIB) 2022 conference. (1st September 2022) - Nanninga, Madelon
Abstract : The Association of Southern African Indexers and Bibliographers (ASAIB) 2022 virtual conference was held on 20 May with the theme of 'Indexing in Service of the Reader'. Madelon Nanninga reflects on her experience joining the conference via Zoom from the Netherlands. She reports that the conference was particularly successful at highlighting not only the needs of readers but also the interconnections between indexers, authors and publishers.